Vestigial-like 2 contributes to normal muscle fiber type distribution in mice - Masahiko Honda (Nature Portfolio, 2017)
Abstract Skeletal muscle is composed of heterogeneous populations of myofibers that are classified as slow- and fast-twitch fibers. The muscle fiber-type is regulated in a coordinated fashion by multiple genes, including transcriptional factors and microRNAs (miRNAs). However, players involved in this regulation are not fully elucidated. One of the members of the Vestigial-like factors, Vgll2, is thought to play a pivotal role in TEA domain (TEAD) transcription factor-mediated muscle-specific gene expression because of its restricted expression in skeletal muscles of adult mice. Here, we generated Vgll2 null mice and investigated Vgll2 function in adult skeletal muscles. These mice presented an increased number of fast-twitch type IIb fibers and exhibited a down-regulation of slow type I myosin heavy chain (MyHC) gene, Myh7, which resulted in exercise intolerance. In accordance with the decrease in Myh7, down-regulation of miR-208b, encoded within Myh7 gene and up-regulation of targets of miR-208b, Sox6, Sp3, and Purβ, were observed in Vgll2 deficient mice. Moreover, we detected the physical interaction between Vgll2 and TEAD1/4 in neonatal skeletal muscles. These results suggest that Vgll2 may be both directly and indirectly involved in the programing of slow muscle fibers through the formation of the Vgll2-TEAD complex.